Respon Pertumbuhan Setek Mucuna terhadap Konsentrasi dan Lama Perendaman Ekstrak Bawang Merah - Enda Sabda Gentri Sembiring; Julaili Irni; Rama Riana Sitinjak; Bayu Pratomo (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2021)
Introduction: This study aims to determine the growth response of Mucuna bracteata cuttings to the concentration and duration of soaking shallot extract. Materials and Methods: This study used a factorial Randomized Block Design (RBD) with two factors, namely: shallot extract concentration (P) consists of 4 levels, include P0= untreated, P1= 10 ml, P2= 20 ml, P3= 30 ml, meanwhile the soaking time (Q) consists of 4 levels, such as Q0= momentarily dipping, Q1= 15 minutes, Q2= 30 minutes, Q3= 45 minutes. The data was processed by ANOVA and if significant, then further tested with Duncan Multiple Range Test (DMRT) at the rate of 5%. Results: The concentration of shallot extract, soaking time and their interaction had a very significant effect on the survival percentage of Mucuna bracteata D.C. cuttings. The highest survival percentage of cuttings of Mucuna bracteata on the effect of shallot extract concentration and soaking time was obtained in the P0Q0, P0Q1, and P3Q2 treatments after the lid was opened at 4 weeks after planting. In the number of leaves also had significant effect in the interaction of two factors